BIPHASIC HYDROGENATION OF EUGENOL WITH RUTHENIUM AND RHODIUM NANOPARTICLES STABILIZED IN IONIC LIQUIDS - Crespo, Isis; Domínguez, Olgioly; Baricelli, Pablo; Borusiak, Margarita; Omaña, Ofelia; Castro, William; Rosales, Merlin (Journal of the Chilean Chemical Society, 2020)
The purpose of this study was to evaluate on the catalytic activity nanostructured systems of ruthenium and rhodium stabilized in ionic liquids derived from imidazole: IL1= butylmethyllimidazole tetrafluoroborate [BMIM][BF4] and IL2= butylmethylimidazole hexafluorophosphate [BMIM][PF6] in the biphasic hydrogenation of eugenol under mild reaction conditions T= 80ºC, P= 100psi during 4 hours. The metallic nanoparticles (NPs-M) were synthesized using the ligand hydrogenation displacement reaction for the ruthenium III tris(acetylacetonate), [Ru(acac)3], and bis-μ-cloro-di(1,5-ciclooctadieno) dirhodium(I), [Rh(COD)Cl]2, showing a mean particle size between (2.00±0.04) nm and (4.0±0.2) nm. The nanostructured systems Rh/IL2, Ru/IL2 and Ru/IL1 show similar activities and different from the Rh/IL1 system. On the other hand, the systems stabilized in the IL1 were more selective towards the formation of the 2-methoxy-4-propylphenol than the systems stabilized in the IL2. Nevertheless, in general, the catalysts were good for hydrogenating eugenol, resulting in Rh/IL1 nanoparticles less reactive than Rh/IL2, Ru/IL1 and Ru/IL2.